Hands-on strategy : the guide to crafting your company's future - Finnie, William C (New York J. Wiley, 1994)
Offering a practical, useful, goal-oriented approach to developing strategies and implementing them for higher sales, profits, and shareholder value, Hands-On Strategy is every executive's survival guide for the 1990s and beyond.\Everyone says that developing and implementing a strategy is important. And almost everyone says that the ideas of the leading thinkers are valuable, but presented in too complex a way for most people to implement. This book provides a new approach. It shows how to make the ideas of the strategy gurus work in the real world. Strategy as taught in the business schools equips managers with many powerful analytical tools, yet offers little guidance in applying strategy to organizations. William C. Finnie, with his impeccable business and academic experience, bridges the gap between the strategy abstractions of MBA programs and the real world of competitive business. He shows managers how to transform an arsenal of strategic weapons into a coherent strategy that will help them win their daily battles for profits and market share.
Age Group: Adult
1. Controlling Your Destiny: The Concept and Nature of Strategy -- 2. Creating the Future: The Four-Cycle Strategy Planning Process -- 3. Know Thyself: The Business Definition -- 4. Determine Your Role: The Three- to Ten-Year Strategic Objective -- 5. Creating a Defendable Position: Generic Strategies -- 6. Meeting Customer Wants: Customer-Driven Strategy -- 7. War and Peace: Competitor-Driven Strategy -- 8. Designing Your Future: The Mission Statement -- 9. Delivering Results: Goal Setting and Three-Cycle Annual Planning -- 10. Winning in the Real World: Top-Down Leadership, Bottom-Up Commitment.
Includes bibliographical references (p. 263-270) and index.
Keywords: Industrial management; Strategic planning